Regional distribution of pulmonary ventilation and perfusion in elderly subjects - Holland, J. (1968)
Using radioactive xenon, we measured the regional distribution of pulmonary ventilation and blood flow in six normal men, whose ages ranged between 65 and 75 yr. The measurements were made in the standing position. The static volume-pressure relation of the lungs was also measured in five of the subjects. The results indicate that by comparison with normal young men: (a) Blood flow to the upper lung zones was increased, although it still remained predominant in the lower zones. (b) Ventilation distribution during a vital capacity inspiration was similar to that seen in young subjects. (c) In five of the six elderly subjects, however, the distribution of ventilation in the resting tidal volume range was not preferential to the lower zones as it was in young men. This was probably caused by airway closure in the lower lung zones. The elderly subjects thus exhibit during normal tidal volume breathing a ventilation distribution pattern similar to that observed in young subjects when breathing at low lung volumes, i.e., near residual volume. This difference is probably due to the combined effect of the loss in elastic recoil of the lungs observed in the elderly subjects and of a decreased resistance to collapse of the aged airways. These findings suggest that in the elderly subjects there is a significant regional ventilation-perfusion impairment during quiet breathing, which may explain in part the reported increase in alveolar-arterial oxygen difference with advancing age.